2012
DOI: 10.1530/eje-11-0729
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and screening of hypothyroidism in pregnancy: results of a European survey

Abstract: Background: Maternal hypothyroidism in pregnancy is associated with several adverse outcomes. The Endocrine Society Guidelines for the management of thyroid diseases in pregnancy were published in 2007; however, impact of the guidelines in routine clinical practice is unknown. Therefore, we have carried out a survey of members of the European Thyroid Association (ETA) to study current practices relating to the management of hypothyroidism in pregnancy. Subjects and methods: In December 2010, we emailed an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 25 publications
4
65
0
3
Order By: Relevance
“…However, focusing exclusively on high-risk pregnancies could leave between one-and two-thirds of women with SChypo undiagnosed (21). A recent questionnaire concerning the clinical practice of screening for thyroid disease in pregnancy included 605 members of the European Thyroid Association (22). Forty-two percent of responders screen all women for TD, 43% perform targeted screening of the high-risk group, whilst 17% do not perform screening.…”
Section: Introductionmentioning
confidence: 99%
“…However, focusing exclusively on high-risk pregnancies could leave between one-and two-thirds of women with SChypo undiagnosed (21). A recent questionnaire concerning the clinical practice of screening for thyroid disease in pregnancy included 605 members of the European Thyroid Association (22). Forty-two percent of responders screen all women for TD, 43% perform targeted screening of the high-risk group, whilst 17% do not perform screening.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, significant variability in diagnostic and therapeutic management have been reported by a questionnaire which assessed management of hypothyroidism during pregnancy in Europe (6). However, even with novel prospective studies, many controversies still exist regarding the most appropriate approach for the L-T 4 dose adjustment in pregnancy (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested, that the cause of isolated hypothyroxinemia is iodine deficiency instead of autoimmune thyroid processes, such as among 56/220 (25.4%) pregnant women with isolated hypothyroxinemia TPO-Ab were detectable in only 7.1% of them (Moleti et al, 2009). Data published so far are not sufficient to recommend thyroxine replacement therapy in this case in pregnancy, although a study analysing questionnaires about the treatment of hypothyroidism during pregnancy filled in by over 600 members of the European Thyroid Society (ETA) showed that 38% of the responders would treat isolated maternal hypothyroxinemia, but the responders' definition of this disorder was not consistent (Vaidya et al, 2012), which reflects the lack of clear definition and management of this state.…”
Section: Iodine Dose (μG/day) Organization and Date Median Urinary Iomentioning
confidence: 94%
“…This definition is not well delineated in the literature, because the reference range of TSH-level varies between large limits according to different authors and the gestational trimester (Vaidya et al, 2012;Glinoer & Abalovich, 2007;Burman, 2009). We have evaluated the TSH-and FT4-values based on the above mentioned normal intervals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation